2021
DOI: 10.1109/led.2021.3072042
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Trapping in Conformal CuO/Si Microholes Array Heterojunction for Self-Powered Broadband Photodetection

Abstract: In this letter, we demonstrate the fabrication of a conformal CuO/Si microholes array heterojunction through the DC reactive magnetron sputtering from a high-purity Cu target. By using the monolayer graphene as the top electrode, the device served well as a self-powered vis-NIR photodetector, showing a high responsivity of 301.5 mA W −1 , specific detectivity of 7.96 × 10 12 Jones and a fast response speed (rise time 9.9µ s and fall time 10µs) upon 530 nm illumination. Compared to its planar counterpart, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The open-circuit voltage ( V OC ) and short-circuit current ( I SC ) variables were measured, as shown in Figure b ( V OC of near 0.15 V and I SC of 196 nA were measured at 365 nm). To examine the RR of our study under the V OC parameter, the result of the ReS 2 homostructure diode is displayed with other references in Figure c. ,,, It shows that this work achieved significant value considering that our device is n–n homostructure. In addition, photoresponsivity ( R ) was calculated to examine the photodetecting performance of the ReS 2 photodiode.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The open-circuit voltage ( V OC ) and short-circuit current ( I SC ) variables were measured, as shown in Figure b ( V OC of near 0.15 V and I SC of 196 nA were measured at 365 nm). To examine the RR of our study under the V OC parameter, the result of the ReS 2 homostructure diode is displayed with other references in Figure c. ,,, It shows that this work achieved significant value considering that our device is n–n homostructure. In addition, photoresponsivity ( R ) was calculated to examine the photodetecting performance of the ReS 2 photodiode.…”
Section: Resultsmentioning
confidence: 70%
“…(b) I SC and V OC under different illumination light sources while applying a 50 mW cm –2 power density and a 10 V gate voltage. (c) Rectification ratio and V OC comparison of various structures. ,,, (d) Zoomed-in view of the I – V curves. I SC stands for short-circuit current, and V OC stands for open-circuit voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4d presents the EQE of the SnTe:Si/Si and SnTe/Si devices measured at room temperature (300 K) as a function of light intensity for the 850 nm light. The EQE is defined as the ratio of the number of charge carriers collected by the device to the number of photons shining on the active area from the exterior laser: [ 36 ] EQE badbreak=false(Iphnormal/qfalse)normal/ goodbreak=false(Iphnormal/q false)(hνnormal/Pin)\[ \begin{array}{*{20}{c}}{EQE\; = ({I_{{\rm{ph}}}}{\rm{/}}q){\rm{/}}\emptyset \; = ({I_{{\rm{ph}}}}{\rm{/}}q\;)\left( {h\nu {\rm{/}}{P_{{\rm{in}}}}} \right)}\end{array} \] where I ph, ∅, h , ν, and P in represent the photocurrent, number of incident photons, Planck's constant, frequency of the incident light, and incident light power on the active area of the device, [ 37 ] respectively. For the SnTe/Si device in Figure 4d, a maximum EQE of 75% is observed at a light intensity of 2.1 mW cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…where I ph, ∅, h, ν, and P in represent the photocurrent, number of incident photons, Planck's constant, frequency of the incident light, and incident light power on the active area of the device, [37] respectively. For the SnTe/Si device in Figure 4d, a maximum EQE of 75% is observed at a light intensity of 2.1 mW cm −2 .…”
Section: Electrical and Photoresponse Characteristicsmentioning
confidence: 99%
“…Kim et al reported on the fabrication of a fast ITO/CuO/Si photodetector [7]. Zhang et al prepared a conformal CuO/Si microholes array heterojunction through DC reactive magnetron sputtering with a maximum responsivity of 0.3 A/W at 530 nm [8]. Salih et al prepared a porous silicon/CuO silicon photodetector by electrochemical etching and pulsed laser deposition, with studying its main parameters [9].…”
Section: Introductionmentioning
confidence: 99%